CD70 Deficiency due to a Novel Mutation in a Patient with Severe Chronic EBV Infection Presenting As a Periodic Fever - Caorsi, Roberta; Rusmini, Marta; Volpi, Stefano; Chiesa, Sabrina; Pastorino, Claudia; Sementa, Angela Rita; Uva, Paolo; Grossi, Alice; Lanino, Edoardo; Faraci, Maura; Minoia, Francesca; Signa, Sara; et al. (Frontiers in Immunology, 2018)
Primary immunodeficiencies with selective susceptibility to EBV infection are rare conditions associated with severe lymphoproliferation. We followed a patient, son of consanguineous parents, referred to our centre for recurrent periodic episodes of fever associated with tonsillitis and adenitis started after an infectious mononucleosis and responsive to oral steroid. An initial diagnosis of periodic fever, aphthous stomatitis, pharyngitis, cervical adenitis (PFAPA) syndrome was made. In the following months recurrent respiratory infections and episodes of keratitis were also observed, together with a progressive reduction of immunoglobulin levels and an increase of CD20+ cells. Cell sorting and EBV PCR showed 25000 copies for 100000 leucocytes with predominant infection of B lymphocytes. Lymph node’s biopsy revealed reactive lymphadenopathy with paracortical involvement consistent with a chronic EBV infection. Molecular analysis of XIAP, SHA2D1A, ITK, and CD27 genes did not detect any pathogenic mutation. The patients underwent repeated courses of anti-CD20 therapy with only a partial control of the disease, followed by stem cell transplantation with a complete normalization of clinical and immunological features. Whole exome sequencing of the trio was performed. Among the variants identified, a novel loss of function homozygous c.163-2A>G mutation of the CD70 gene, affecting the exon 2 AG-acceptor splice site, fit the expected recessive model of inheritance. Indeed, deficiency of both CD27, and, more recently, of its ligand CD70, has been reported as a cause of EBV driven lymphoproliferation and hypogammaglobulinemia. Cell surface analysis of patient-derived PHA-T cell blasts and EBV-transformed lymphoblastoid cell lines confirmed absence of CD70 expression. In conclusion, we describe a case of severe chronic EBV infection caused by a novel mutation of CD70 presenting with recurrent periodic fever.se of CAEVB caused by CD70 deficiency and presenting with recurrent periodic fever.